A new species of Ancylomenes Okuno & Bruce, 2009 (Crustacea: Decapoda: Pontoniinae) from the Kimberley region, Western Australia - Bruce, A. J. (Zootaxa, 2011)
The pontoniine shrimp genus Ancylomenes Okuno & Bruce, 2009 now includes 17 Indo-West Pacific species (Okuno & Bruce 2009). With a few exceptions, such as A. aesopius (Bate, 1863) and A. longicarpus (Bruce & Svoboda, 1983), these present a highly consistent morphology, differing at species level principally in details of the rostrum, third abdominal somite, ophthalmic process, dentition of the second pereiopod chelae, and ambulatory propods and dactyls. This consistency renders detailed descriptions repetitive and largely redundant.